Sinistral transpression and the Silurian closure of Iapetus - Soper, N. J.; Strachan, R. A.; Holdsworth, Robert E.; Gayer, Rodney A.; Greiling, Reinhard O. (Journal of the Geological Society, 1992)
In recent years conflicting models have been proposed for the late Caledonian closure of the Iapetus ocean between Laurentia, Baltica and the Avalonian terranes. Recently published structural and stratigraphic evidence from Britain, Scandinavia, East Greenland and Newfoundland is reviewed and shows that Western Avalonia, Eastern Avalonia and Baltica all docked sinistrally against Laurentia in the Silurian. - Western Avalonia collided sinistrally against the previously accreted Gander and Dunnage arc terranes on the Appalachian margin of Laurentia in mid-Silurian time and then shifted dextrally during the Acadian orogeny in the Devonian. Oblique collision of Baltica with the Greenland margin induced southeasterly crustal stacking in the Scandian orogen and sinistral transpression in the NE Greenland Caledonides, and was followed by more nearly orthogonal convergence. Eastern Avalonia underwent anticlockwise with the Scottish ‘corner’ of Laurentia, rotating into a re-entrant between Laurentia and Baltica. - Some implications of this Silurian closure model are that convergence in the Tornquist zone was modest at that time, and that the Acadian (Devonian) deformation in the northern Appalahians and Britain had a subsequent external cause, most likely the impingement of Armorica and Iberia due to the northward drift of Gondwana.